2021
DOI: 10.1186/s12958-021-00850-w
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-194 is increased in polycystic ovary syndrome granulosa cell and induce KGN cells apoptosis by direct targeting heparin-binding EGF-like growth factor

Abstract: Background Polycystic ovary syndrome (PCOS) is an endocrine-related follicular developmental disorder that affects 50 %-70 % of reproductive-aged women diagnosed with ovulation-related infertility. Abnormal proliferation and apoptosis of granulosa cells (GCs) are thought to be the critical factors leading to abnormal maturation of follicles. It has been shown that microRNAs (miRNAs) exert a significant influence in the pathogenesis of PCOS; however, the relationship between miRNA, PCOS, and GC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The results are expressed as the mean ± SEM of at least three independent experiments. Values that are statistically different from one another (p < 0. and in the ovaries of PCOS rats [32]. Our results showed that StAR expression was upregulated by HB-EGF in hGL cells.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The results are expressed as the mean ± SEM of at least three independent experiments. Values that are statistically different from one another (p < 0. and in the ovaries of PCOS rats [32]. Our results showed that StAR expression was upregulated by HB-EGF in hGL cells.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, future studies will need to confirm the protein levels of HB-EGF in human follicular fluid. The mRNA levels of HB-EGF are downregulated in the granulosa cells of PCOS patients and in the ovaries of PCOS rats [ 32 ]. Our results showed that StAR expression was upregulated by HB-EGF in hGL cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study exhibited the elevation of HB-EGF level in follicular fluid from PCOS women. Meanwhile, aberrant HB-EGF expression was also noted in PCOS patient GCs [18]. Together these observations imply a potential involvement of HB-EGF in PCOS etiology.…”
Section: Discussionmentioning
confidence: 63%
“…For example, Gao et al showed that the level of serum EFG in the abortion PCOS patients was higher than that in the successful delivery PCOS patients, moreover, EFG was an independent factor which affecting and positively correlated with the pregnancy outcome of PCOS patients (26). Mechanistically, in a recent study by Wu and colleagues, they found that high expression of microRNA-194 in granulosa cell of PCOS patients could induce KGN cells apoptosis by direct targeting heparinbinding EGF-like growth factor (27). More recently, Huang and co-workers indicated that heparin-binding-EGF might induce mitochondrial dysfunction and granulosa cells apoptosis through advancing estrogen hypersecretion dependent on c A M P -P K A -J N K/ E R K -C a 2 + -FOXO1 pathway (2 8 ).…”
Section: Discussionmentioning
confidence: 99%